DEVELOPMENT OF POETRY FLASHCARDS ON THE GOOGLE SITES (GOSIFAN) TO IMPROVE THE RHYMING SKILLS OF GRADE FIFTH ELEMENTARY SCHOOL STUDENTS USING THE STAD LEARNING MODEL - Pinasti Putri Ananta Maulida; Petra Kristi Mulyani (Prima Magistra: Jurnal Ilmiah Kependidikan, 2025)
The purpose of this study was to determine how Gosifan to improve fifth graders rhyming skills using STAD. This study used the Research and Development (R&D) method. The subjects of this study were 28 fifth graders. Data collection techniques in this study were observation, interviews, documentation, and tests. Interview to homeroom teacher showed the use of technology was limited to YouTube and slides. Gosifan was developed with expert validation on media in very qualified criteria meaning that interactive, appropriate orientation videos, and there are quizzes to help students understand. Expert validated the content of media in very qualified criteria meaning that media material aligns with the curriculum elements and learning outcomes, helping students understand rhymes in poetry. Expert validated instructional materials in very qualified criteria meaning that the learning objectives are suitable with goals learning. Teacher questionnaire showed very qualified criteria in explaining interesting the materials. Students questionnaire showed very qualified criteria meaning that attractive media design with easily understandable language. The Paired Samples Test revealed an effect from the application of Gosifan (Google Sites Flashcard Pantun) with a 2-tailed sig value of 0.00 on poetry material. In the large-scale test, the average pre-test score was 61.14, and the post-test score was 82.27, showing an effect before and after the media application. The N-Gain score of 0.59 falls in the moderate category, and the average N-Gain value of 60.21% is considered fairly effective. Poetry Flashcard in Google Sites can helped students to improve rhyming skills.